The Democratisation Failure in the Middle East: Causes and Prospects - Karimi, Sirvan (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
It has almost become conventional wisdom among analysts and experts on Middle Eastern politics to relate the fate of the democratisation process and its failure in the region to the foreign policy platforms of the USA and its Western allies. Contrary to the prevailing interpretations of democratisation failure in the Middle East, it will be argued that the historical proclivity of leftist organisations and parties to conflate anti-imperialism with fostering hostility towards liberal values, the limited scope of industrialisation, and culturally and religiously ingrained competing loyalties are factors that have cumulatively made a significant contribution to the cultivation of a socio-political environment that is not receptive to democracy.